Processos e políticas de formação em cursos de mestrado em Comunicação na Região Norte do Brasil - Adrian, Alessandra Bonfim Bacelar de Abreu (2019)
The present dissertation deals with the training processes and policies in masters programs in communication in the northern region of the country, specifically in the Federal Public Universities UFT, UFAM, UFPA based on the texts contained in the institutional websites and the Quadrennial Evaluation carried out by CAPES. The main objectives were to analyze how the curricular matrices of stricto sensu postgraduate courses in communication in the northern region of Brazil are structured, observing the occurrence of changes over the years and if they occurred, what motivation, and whether they are in line with the transformations occurring in the world, in view of the growth of the internet and the new mechanisms that have emerged for the exercise of the profession. For this purpose, the bibliographic research was used, making a rescue on the history of postgraduate studies in Brazil, the creation of CAPES and the transformations that occurred to improve higher education in the country, as well as the mechanisms for monitoring the quality of the programs in operation, an analysis of the evaluations carried out in recent years, which allowed us to perceive the still scarce number of doctors and the same courses in the northern region of Brazil, which directly implies difficulties and longevity of some programs in view of the difficulties of aligning curricular matrices with the local reality. It is concluded that in the northern region, the masters programs in communication are a combination of efforts for the provision of training, which have a large faculty and sometimes can not meet what has been proposed, but which amidst the difficulties seek to understand the and continue to operate and promote knowledge, even if still very dissonant of the demands of the labor market, and the transformations that have occurred in other countries that seek to combine quality training in a shorter time and with the purpose of promoting development.